PEMBERIAN MP-ASI DAN STATUS GIZI BAYI USIA 6-24 BULAN BERDASARKAN INDEKS BB/U DI DESA BAN KECAMATAN KUBU TAHUN 2014 - Muhammad Akmal Hakim (DiscoverSys Inc., 2015)
The provision of complementary foods (solids) early or too late will cause the baby susceptible to infectious diseases, allergies, nutritional deficiencies, and excess nutrients, which can lead to malnutrition and impaired growth. This research is to know the description the provision of complementary feeding and nutritional status of infants aged 6-24 months.This study was a cross sectional study in Public Healthcare Centre (Puskesmas) Kubu II with a sample of 81 people were selected by convenient sampling. As the sample is domiciled in infants Puskesmas Kubu II, and the exclusion criteria are infants with chronic infections, chronic diseases, congenital abnormalities and neurological defects. Data collection using questionnaires to a sample of parents selected as responders and weight measurements of the samples. Data analysis was performed univariate and bivariate. The result is from 81 samples obtained 59 samples were not given timely complementary feeding. Malnutrition status was found in 1 sample and 80 samples with good nutrition. Judging from the trend level of education and the provision of complementary feeding accuracy, the lower the level of research increasingly imprecise provision of complementary feeding. From the group of mothers with a high education level, 88.1% did not provide timely complementary feeding. In granting the accuracy of the distribution of complementary feeding on the nutritional status, the provision of timely complementary feeding not found one case of malnutrition (1.7%) and 58 well-nourished (98.3). While the provision of timely complementary feeding found 22 cases of good nutrition (100%).